The Utilization of Milk as a Catalyst Material in Enzyme-Mediated Calcite Precipitation (EMCP) for Crack-Healing in Concrete - Zalfa Maulida Ihsani; Heriansyah Putra (Institute of Research and Community Outreach - Petra Christian University, 2021)
This study discussed the applicability of the calcite precipitation method to repair the concrete's crack. The grouting solution of Enzyme-Mediated Calcite Precipitation (EMCP) was modified by adding milk as a catalyst in calcite formation. Cracks in concrete samples were made when the concrete was 28 days with a width of 0.1-0.3 mm. The EMCP solution composed of urease, urea, CaCl2, and milk was injected into the cracked concrete sample, and its effect on permeability and compressive strength tests were evaluated. The result shows that the optimum composition of milk used in the formation of calcite had a concentration of 5 g/L with an initial preparation temperature of 70oC, which produced 26% higher than the initial EMCP solution. The mechanical test results show that the reduction of coefficient of permeability of 92.23% compared to the cracked sample and the improve strength up to 98.75% of the non-cracked sample were obtained by three circles injection. This study elucidated that milk utilization as a catalyst material in repairing cracks with the EMCP method is a potential method for crack-healing concrete.